Seasonal effect on physiological and haematological profiles, scrotal circumference and testicular parameters in indigenous goat bucks under tropical humid island ecosystem - PERUMAL, P; SUNDER, JAI; MISHRA, P C; DE, A K (The Indian Journal of Animal Sciences, 2022)
Andaman local goat (ALG) is meat animal in Andaman and Nicobar islands (ANI) of India. Present study was conducted to measure the seasonal effect on physiological and haematological profiles, scrotal circumference (SC) and testicular weight during rainy and dry summer seasons in ALG. A total of 10 adult intact ALG bucks (body condition score: 3.0-3.5 and classified as good; 3-4 years) were selected from the goat breeding farm, ICAR-CIARI, Port Blair, ANI, India. Results revealed that these experimental profiles differed significantly (p < 0.05) between the seasons. Significantly (p < 0.05) higher haematological profiles, SC and testicular weight were observed in rainy season than in dry summer season whereas physiological profiles such as rectal, skin and scrotal temperatures were higher in dry summer than in wet rainy season. The study concluded that the rainy season has significantly greater beneficial effects than dry summer season on reproduction and artificial breeding programmes in semi-intensive management of goat in the present location.